A flexural design methodology for UHPC beams posttensioned with unbonded tendons. (15th March 2020) - Dogu, Mehmet; Menkulasi, Fatmir
Highlights: A method for predicting flexural behavior of posttensioned UHPC beams is proposed. A mechanics based phenomenological model is presented to predict flexural capacity. Equations for predicting strand stress at the ultimate limit state are developed. Predictions match well with results from validated numerical simulations. A method to characterize the failure mode is presented. Abstract: This paper provides a framework for predicting the flexural behavior of ultra-high performance concrete (UHPC) beams posttensioned with unbonded tendons. A mechanics based phenomenological model is presented to predict flexural capacity, and a set of equations that can be used to predict strand stress at the ultimate limit state is proposed and considers how the nonlinear domain of UHPC in tension affects flexural behavior. It is demonstrated that predictions based on the proposed equations and the presented flexural design methodology are in close agreement with results obtained from validated numerical simulations. The strand stress at ultimate is expressed as a function of neutral axis depth, effective depth of tendon, tendon length, loading configuration, loading pattern, plastic hinge length, maximum usable UHPC compressive and tensile strain, and shape of the stress-strain curve of the tendon. The influence of tendon area, mild steel area and yield stress, specified UHPC compressive strength and tensile strength, as well as beam cross-sectional dimensions are captured indirectly through the calculation of the neutral axis depth. The flexural design methodology is presented in terms of the failure mode observed when the considered specimens reach their ultimate load carrying capacity. The failure mode is characterized as either a fiber tension controlled failure or a UHPC compression controlled failure. The change in strand stress at the ultimate limit state, Δfps, the strand stress at the ultimate limit state, fps, and the nominal moment capacity, Mn, of 221 UHPC posttensioned beams obtained based on the proposed methodology are compared with results obtained from validated numerical models and it is demonstrated that average predicted values are within 5% of computed ones and the coefficient of variation is not greater than 17%.